Identification of KPC-Producing Pseudomonas aeruginosa and Acinetobacter baumannii in a Burned Infant: A Case Report - Leila Azimi; Reza Alaghehbandan; Masoud Mohammadpoor; Abdolaziz Rastegar-Lari (Journal of Medical Bacteriology, 2015)
The objective of this study was to determine the phenotypic characteristics of KPC-producing Pseudomonas aeruginosa and Acinetobacter baumannii isolates. A case report study was performed at a tertiary burn care centre in Tehran,  Iran.  Nine  isolates  of Pseudomonas  aeruginosa  and  Acinetobacter baumannii from a hospitalized case were isolated. The identity of isolates was confirmed and their antibiotic susceptibility testing was performed. Eight out of nine Pseudomonas aeruginosa and Acinetobacter baumannii isolates were resistant to Imipenem.  Three out of 8 imipenem  resistant isolates were also positive for KPC test. Findings of this study highlight the importance of implementation  of an effective infection control strategy in order to prevent and reduce the emergence and spread of gram negative Carbapenemase- producing organisms in Iran.